(untitled) (Heritage, 2026)
Modern technologies have enabled the expansive development of various forms of terrorist activity. As one of the forms of use of modern technologies, the example of unmanned aerial vehicles, better known as "drones", is cited, which can be used for both military - operational and tactical purposes, but can also have a very widespread application for the activities of various terrorist and paramilitary organizations. A special problem that arises here is that the use of these unmanned aerial vehicles is becoming increasingly accessible today, and the prices of purchasing these devices are no longer as high as before. Also, these devices are becoming increasingly accessible to various paramilitary organizations, which openly use them to achieve their illegal goals. A particular security risk today is the use of artificial intelligence, which can be considered one of the most dangerous tools in the hands of terrorists or criminal organizations. The algorithms that artificial intelligence has at its disposal are both capable of causing great damage and of being a powerful weapon in the hands of terrorism and crime.